The IPT futsal league / Muhammad Azli Mohd Saadan and Muhammad Azwan Mohd Azmi - Mohd Saadan, Muhammad Azli; Mohd Azmi, Muhammad Azwan (Universiti Teknologi MARA, Negeri Sembilan, 2023)
The IPT futsal league is a competitive league with levels based on team qualifications. The main league is the Super League, while the Premier League is for men's futsal and the Women's Futsal League is for women. The league is the second largest in the country and has established rules, making it the second-largest league after the MPFL. It produces talented players, allowing young players to shine in futsal and make futsal a career. The league also promotes good-thinking athletes, distinguishing between good and bad attitudes, giving them an advantage over others. In the context of sports (athletes, leagues, teams, events), sponsorship is characterized as a substitute for supporting promotional goals. Sports sponsorship is a useful strategy for expanding markets and retaining current clientele. Through sponsoring the IPT Futsal League, Extravaganza Futsal collaborates with the IPT Futsal League to ensure its success. Extravaganza Futsal has been granted permission by the IPT Futsal League to set up shop at each location for competitions. Each team and volunteer that plays in the IPT Futsal League receives a unique shirt from Extravaganza Futsal, which is supported by the university. Extravaganza Futsal also provides unique merchandise for the IPT Futsal League to attract customers. like shoes, socks, hats, and other accessories. Each player's university-specific apparel is for sale at the accessible booths.